Neue Antidiabetika und kardiovaskuläre Outcome-Studien - Seufert, Jochen; Laubner, Katharina (Diabetologie und Stoffwechsel, 2017)
Type 2 diabetes mellitus (T2DM) represents a major risk factor for the development of cardiovascular events, and cardiovascular mortality determines overall mortality in these patients. So far, glucose lowering per se has demonstrated a small effect in reduction of cardiovascular risk in T2DM patients. Due to regulatory purposes, since 2008 all novel antidiabetic medications, such as DPP4 inhibitors, GLP-1 receptor agonists and SGLT2 inhibitors are investigated in dedicated cardiovascular outcome trials to demonstrate cardiovascular safety (non-inferiority trials). While the currently completed cardiovascular outcome trials for the DPP4 inhibitors sitagliptin, saxagliptin and alogliptin consistently demonstrated a neutral effect on cardiovascular risk, those trials for the GLP-1 receptor agonists revealed differential outcomes. Lixisenatide effects were neutral on cardiovascular outcomes while Liraglutide and Semaglutide demonstrated a reduction in cardiovascular risk. Most impressively was cardiovascular mortality, overall mortality and hospitalisation for heart failure reduced by the SGLT2 inhibitor empagliflozin in its dedicated outcome trial. These results strongly imply that certain novel antihyperglycaemic agents bear the potential to strongly reduce cardiovascular risk in patients with T2DM beyond their glucose lowering potency. The potential to reduce cardiovascular risk in patients with T2DM will selectively determine the clinical application of antidiabetic medications in the future.
Keywords: neue Antidiabetika; kardiovaskuläres Risiko; Diabetes mellitus Typ 2